Availability, Biomass Yield, and Nutritional Values of Fodder Tree Leaves in Mirab Abaya District in Southern Ethiopia - Kodo, Wogaso; Tadele, Yilkal (Jordan Journal of Agricultural Sciences, 2024)
The study was carried out to assess the availability; fodder yield and nutritional values of selected fodder tree leaves. Household surveys, field measurements, and laboratory analyses were used to generate the data. Survey data was collected from randomly selected 138 respondents using a pre-tested structured questionnaire. Eleven, 18, and 13 fodder trees respectively in highland, midland, and lowland were identified and ranked. A total of 12 top-ranked fodder tree species were considered for leaf yield estimation and laboratory analysis. The average leaf yields (kg DM) per tree of the selected fodder species ranged from 15.96 for Rhus natalensis in the lowland to 128.43for Erythrinabrucei in the highland and varied significantly (P < 0.05) among the species. The crude protein /CP/ content (g/kg DM) was highest for Erythrinabrucei (198.3) and was least in Psydrax schimperiana (151). The highest Ether Extract /EE/ was observed in Mystroxylon aethiopicum (18.66 g/kg DM) and the lowest was noted in Nuxiacongesta (13.36 g/kg DM). The neutral detergent fiber/ NDF/ was highest for Arundinaria alpine (602g/kg DM) and least in Psydrax schimperiana (297.4g/kg DM). There were no significant differences in condensed tannin content among the fodder trees studied. Oxalate values ranged from 18.4g/kg DM in Terminalia brownii to 36.5 g/kg DM in Balanites aegyptiaca. Generally, the differences in leaf yield and nutrient contents between different fodder species were significant (p<0.05). From the results of this study, it can be concluded that the fodder tree species can be considered a potential source of CP to supplement poor-quality roughages to fill the gap.